Proposta do Kernel Sigmoide (KSIG) e sua análise de convergência para a solução de problemas de filtragem adaptativa não linear - Silva, Éden Pereira da (2017)
Adaptive filtering is applied as solution for many problems in engineer. There are many techniques to improve adaptive filtering as kernel methods and, in addiction, it is used a pretuned dictionary. In this context, here is presented the KSIG algorithm, the kernel version of Sigmoide, where is used the kernel, to decrease the error, and the non-linear and even cost function to increase the convergence speed. Here it is described also, the KSIG with a pretuned dictionary, to reduce the size of the data set used to calculate the filter output, which is a kernel method consequence . The KSIG and KSIG with pre-tuned dictionary theoretical efficiency is one result of their convergence proof, which evidence that the algorithms converge in average. The learning curves, which are results of some experiments, show that when KSIG and KLMS algorithms are compared, the first converges faster, in less iterations, than the second, in the version with and without pre-tuned dictionary of both algorithms.